الرحمة و ثمرتها في الدعوة إلى الله تعالي - الراشدي، ياسر محمد عبدالله (ديوان الوقف السني - مركز البحوث والدراسات الاسلامية, 2014)
Mercy was derived from the most compassionate, most merciful, and they are adjectives to all mighty (Allah) , so the mercy was great manner described for our generous Prophet who is the best example for all people ,and everyone who in charge and has responsibility should have this manner . And this was assured by the Holly Quran verses and (Hadith) which they called for mercy behavior in calling Allah ,because what you get is bigger and much than other calling ways . The way of mercy in calling has to be even in anger and best example in such manner was the generous Prophet (PBUH) who emphasized on mercy in his talks and actions.,, let us not forget that merciful calling was written to be continuous until Judgment Day and it has positive effects, mental relief and it brings peace and security among callers, and this if indicates for something, it indicates that Islam is the religion of mercy, care and peace
Keywords: الدعوة إلى الله -- الدعاة المسلمون -- الرحمة